Development of Mind Mapping Based Prezi Multimedia to Improve History Learning Outcomes - Renita Agustina; Ajat Sudrajat; Johan Setiawan; Ninik Sudarwati (Ta'dib, 2022)
The purpose of the study was to develop, test the feasibility, and test the effectiveness of Mind Mapping-based Multimedia Prezi Next Online on Hindu-Buddhist history materials in Indonesia for students of history education at Yogyakarta State University. This research is a Research and Development, 4D model (Define, Design, Develop, Disseminate). Data collection techniques consisted of interviews, questionnaires, and tests. Data analysis techniques are in the form of preliminary studies and product feasibility. Product effectiveness analysis test for normality, homogeneity, and effectiveness. The results of the research are: (1) Developing a Multimedia Prezi Next Online product based on Mind Mapping for learning the history of materials from the Sriwijaya Kingdom. (2) The results of the feasibility of the material get 48 points and are in the appropriate category. The media aspect was assessed by media experts to get an overall score of 68, which is in the very decent category. (3) The results of the effectiveness of N-Gain describe the effectiveness of developing Mind Mapping-based Prezi Next Online with materials from the Sriwijaya Kingdom, this is indicated by an increase in learning outcomes in the classroom using Mind Mapping-based Prezi Next Online Multimedia. The use of Multimedia Prezi can deliver more interesting material and the learning process will be more fun and easy to understand.